Curricula: What can the School do for the Development of a Child - Dewan, Hardy K (Voices of Teachers and Teacher Educators, 2017)
Schools have a multiplicity of roles and are influenced by a diverse set of stakeholders. The interests of these stakeholders and their perspectives are not always aligned. Besides since the school only offers a part of the education experience and claims to fulfill only some of the purposes that the society had from the education of its children, the role of the school and the curriculum that drives it becomes important to interrogate. To what extent it should further the ideas prevalent in that community and that particular society and to what extent must it bring in new ideas and induce change even in that society. The rapid pace of technological changes and the pressures has led to a direction of interaction where lot of people are thrown together and mixed but yet they remain in their boundaries. We point out that the direction of development and construction of the market forces the preferences, desires and aspirations in a direction that is competitive, individualistic and narrow. In contrast to this popular notion of school, democratic polity requires a curricular process that is inclusive and brings in the diversity of the experiences the children need to develop holistically and also ensure all children can participate and engage with others from different backgrounds. The school needs to make children learn to engage with each other, co-operate and learn with, about and from each other. The other important expectation from the school is to help children become curious, confident learners and know how to judge what they come across in their life for its worth and relationship to reality. In the current times we need to rediscover the philosophy that built a democratic human society and draw implications for education from that.